Dicer Partner Proteins Tune the Length of Mature miRNAs in Flies and Mammals - Fukunaga, Ryuya (2012)
Drosophila Dicer-1 produces microRNAs (miRNAs) from pre-miRNA, whereas Dicer-2 generates small interfering RNAs (siRNAs) from long dsRNA. Alternative splicing of the loquacious (loqs) mRNA generates three distinct Dicer partner proteins. To understand the function of each, we constructed flies expressing Loqs-PA, Loqs-PB, or Loqs-PD. Loqs-PD promotes both endo- and exo-siRNA production by Dicer-2. Loqs-PA or Loqs-PB is required for viability, but the proteins are not fully redundant: a specific subset of miRNAs requires Loqs-PB. Surprisingly, Loqs-PB tunes where Dicer-1 cleaves pre-miR-307a, generating a longer miRNA isoform with a distinct seed sequence and target specificity. The longer form of miR-307a represses glycerol kinase and taranis mRNA expression. The mammalian Dicer-partner TRBP, a Loqs-PB homolog, similarly tunes where Dicer cleaves pre-miR-132. Thus, Dicer-binding partner proteins change the choice of cleavage site by Dicer, producing miRNAs with target specificities different from those made by Dicer alone or Dicer bound to alternative protein partners.